If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -65 = 13 Reorder the terms: -65 + z = 13 Solving -65 + z = 13 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '65' to each side of the equation. -65 + 65 + z = 13 + 65 Combine like terms: -65 + 65 = 0 0 + z = 13 + 65 z = 13 + 65 Combine like terms: 13 + 65 = 78 z = 78 Simplifying z = 78
| 8x+6y=-6 | | 6y-10=-2(y+9) | | 4(4x-7)-8=4(x-4)+40 | | -4(-8+x)=20 | | U^2+u-42=0 | | (3x^2*y+y^2)dx+(3x^3-y^2+4xy)dy=0 | | 60-m=48 | | 27m=81 | | 3y-10+7y=20 | | 4m+3=40 | | u^2=64 | | -5x-19-2x-9=28 | | b-87=75 | | a+57=220 | | X-3x-5x=49 | | 9+6c-2c= | | xy(3x+2y)=4 | | 20=570+10x | | 11500*x=250000 | | 2y-10=12 | | 10000*x=250000 | | 20=(570-10x) | | 7+2(3x-1)=8x-3(2x+15) | | 33=5y-17 | | y-50=25 | | 0=r^2-282.24 | | 4+2p=10(3/5p-2) | | 7z+3=29(z-6) | | E^4x+5=6 | | 5v=72-3v | | 2y+3=7y-4 | | 15=x+16 |